2006
DOI: 10.1057/palgrave.ap.5500151
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electoral Reform on Women's Representation

Abstract: One concern about reform of the electoral system in the Netherlands is whether this would reduce the proportion of women members in the House of Representatives. What evidence is there for this expectation? This study considers these issues, with the first section summarizing the normative arguments why socially inclusive legislatures are thought to be desirable. The representation of women in the Netherlands parliament is compared against the record in other countries worldwide. The second section analyzes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 26 publications
(16 reference statements)
0
50
0
23
Order By: Relevance
“…Em sistemas majoritários, especialmente onde apenas um candidato se elege por distrito, normalmente os eleitos não obtêm a maioria dos votos válidos. Por causa disso, os votos de segundos e terceiros candidatos -os menos competitivos -acabam não sendo aproveitados na composição dos legislativos; como muitos candidatos que representam grupos politicamente minoritários frequentemente não conseguem grande volume de votos, isto significa que, na prática, eles acabam sendo sub-representados (Norris 2006;Reynolds 1999). Esta distorção entre votos e eleitos, embora varie de acordo com diversas características, seria menor em sistemas com maior magnitude eleitoral, onde justamente mais cadeiras são alocadas por distrito e, por consequência, candidatos menos competitivos têm maiores chances de se eleger (Reynolds 1999, p.555;Schwindt-Bayer 2010, p.46).…”
Section: Ii2 O Efeito Da Magnitude Eleitoral Na Representação De Muunclassified
See 2 more Smart Citations
“…Em sistemas majoritários, especialmente onde apenas um candidato se elege por distrito, normalmente os eleitos não obtêm a maioria dos votos válidos. Por causa disso, os votos de segundos e terceiros candidatos -os menos competitivos -acabam não sendo aproveitados na composição dos legislativos; como muitos candidatos que representam grupos politicamente minoritários frequentemente não conseguem grande volume de votos, isto significa que, na prática, eles acabam sendo sub-representados (Norris 2006;Reynolds 1999). Esta distorção entre votos e eleitos, embora varie de acordo com diversas características, seria menor em sistemas com maior magnitude eleitoral, onde justamente mais cadeiras são alocadas por distrito e, por consequência, candidatos menos competitivos têm maiores chances de se eleger (Reynolds 1999, p.555;Schwindt-Bayer 2010, p.46).…”
Section: Ii2 O Efeito Da Magnitude Eleitoral Na Representação De Muunclassified
“…Mulheres não só ocupam menos cargos institucionais, mas também eletivos, e isso mesmo em democracias consolidadas (Reynolds 1999;Norris 2006;Schwindt-Bayer 2010;Roberts, Seawright & Cyr 2012;Sacchet 2013). Inevitavelmente, isto impõe problemas à democracia.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Mens kvinderepraesentationen i gennemsnit var 20 % i lande med forholdstalsvalg, var den kun 11 % i lande med pluralitets-/majoritetsvalg som f.eks. det engelske, og endelig 14 % i lande med blandede valgsystemer (Norris 2006). Valgsystemets betydning for kvinderepraesentationen ser dog ud til at vaere mindre i ikkevestlige end i vestlige lande (Norris 2004).…”
Section: Nye Forklaringerunclassified
“…There is no doubt about the women capability even in the politics speaks but they are not doing enough for the other women politicians as highlighted by (Ferreira, 2014) that female once become elected have more ability to be re-elected as compare to their counterpart male candidate and this has not any positive impact over the other females to win in the election. Earlier researchers have found that women is the only component of the social diversity and in the light of Eastern Europe, North America and Scandinavia countries studies he has found that the under representation of women's has caused a great positive impact on the public policies and an issue for the democratic setup of these governments (Norris, 2006). Górecki & Kukołowicz (2014) have found that the mandatory quotas for bringing more women in parliament have shown a considerable increase of the women but at the same time this has shown a fast down fall in their performance regardless of their past background of experiences.…”
Section: Political Issue and Gender Capabilitymentioning
confidence: 99%